PEMANFAATAN LIMBAH PADAT TANDAN KOSONG KELAPA SAWIT DAN TANAMAN PAKIS-PAKISAN UNTUK PRODUKSI KOMPOS MENGGUNAKAN AKTIVATOR EM-4 - Rudi Rahmadi; Amir Awaluddin; Itnawita ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
The composting process using  oil palm solid wastes (EFB),  palm oil mill effluent (POME), fern tree using effective microorganism 4 (EM 4) has been  conducted and this would facilitate  reduction of  the wastes from palm oil industry. The aim of this research was to find the best formulation using oil palm wastes, ferns, and EM 4 in producing a composted  material. The quality of compost was determined according toits pH, water content and C/N ratio at each 5 days for 30 days composting period. The water content of sample was determined using Gravimetri methode, while total-N was analyzed by Kjeldahl methode. The result indicated  that  co-composting of EFB andferns  using POME and EM-4 as the activators didn’t have  significance difference compared with that of  the composting products with the value of P>0,05. The value of pH, water and C/N ratio of composting products were respectively 7-8, 40-60% and 1314, following 30 days composting period.